(3QSGdI aj cdeI GdTgGOI hHjGf EYQGHgG heYfGgGs - (3MSf Hf eMeO GdSYjO GdYHGSjs
(3ChdgG (B:s
(3GdMeO ddg GdeSJMb ddYHhOjI Ydi GdEfaQGO CeG HYO ajbhd deG CTGQ Ydi GdSjO CMeO GHh eMeO CHh GdMGQK s
(3BNQgG (B:s
(3efUhH GdeMd Ydi Cfg eaYhd CTgO hgh eY eYehd LedI eYWhaI Ydi LedI hUdi Gddg NjQ GdCfGe hCUMGHg GdcQGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HghGeTgG JYdjbGJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs